Availability, cost and affordability of selected antibiotics and antiviral medicines against infectious diseases from 2013 to 2019 in Nanjing, China. Issue 5 (4th March 2021) - Zhu, Yulei; Xu, Xinglu; Fang, Wenqing; Wang, Ying; Dai, Huizhen; Li, Xin
Abstract: Objectives: As economic globalisation develops in‐depth, infectious diseases that occur in a country or region no longer remains a regional issue. Antibiotics and antiviral medicines are essential medicines for the therapy of infectious diseases. This study aims to evaluate their availability, cost and affordability of AaAMs against infectious diseases in 41 public hospitals from 2013 to 2019 in Nanjing, China. Methods: Data on the availability and price of 17 antibiotics and 6 antiviral medicines in 41 public hospitals were obtained from the Jiangsu Institute of Medicine Information. We adopted the WHO/Health Action International method to measure the availability, cost and affordability of these medicines. Results: The availability of selected medicines against infectious diseases was relatively low; the median availability of originator brands was near‐zero and that of lowest‐priced generics during the survey period less than 50%. The total availability of medicines was poor in primary hospitals as compared to secondary and tertiary hospitals. The median daily‐defined dose cost of originator brands was expensive (range from 66.11 RMB to 107.83 RMB), whereas that of lowest price generics was fairly acceptable at < 8 RMB. The affordability of most surveyed medicines was reasonable, which showed significant improvement over time, but the daily cost of a few medicines for originator brands exceeded the average daily wage. Conclusions: In general, the affordability of medicines surveyed was acceptable, while the availability was too low. There should be a great concern for improving the reserve system of anti‐infective medicines in healthcare institutions. Policy should focus on improving the availability of generic drugs in hospitals and encouraging preferentially prescribed.